1999
DOI: 10.1111/j.1600-0773.1999.tb00073.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Bifemelane on Incomplete Cerebral Ischaemia‐Induced Reduction of Long‐Term Potentiation in Rat Hippocampal Neurones in vivo

Abstract: Abstract:In the present study, we investigated the effects of bifemelane on the reduction of hippocampal long-term potentiation after transient ischaemia. Bilateral common carotid arteries were clamped for 10 min. in halothane-anaesthetized rats. Thirty min. before occlusion, bifemelane (25 mg/kg, intraperitoneally) or saline was administered to the rats. Four days after occlusion, we measured long-term potentiation in Schaffer collateral-CAl synapses and perforant pathdentate gyrus synapses in v i v a Long-te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2007
2007

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…The hippocampus is well known to be one of the most vulnerable brain regions to ischaemia. Previous reports have shown that hippocamal LTP formation is significantly impaired by incomplete cerebral ischaemia and is accompanied by no histological change and that it can be rescued by pharmacological interventions including brain metabolic stimulants and a radical scavenger [16][17][18].…”
Section: Introductionmentioning
confidence: 98%
“…The hippocampus is well known to be one of the most vulnerable brain regions to ischaemia. Previous reports have shown that hippocamal LTP formation is significantly impaired by incomplete cerebral ischaemia and is accompanied by no histological change and that it can be rescued by pharmacological interventions including brain metabolic stimulants and a radical scavenger [16][17][18].…”
Section: Introductionmentioning
confidence: 98%